2005
DOI: 10.1021/ja042924i
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Water Soluble Single-Walled Carbon Nanotube Graft Copolymers

Abstract: Poly(aminobenzene sulfonic acid) (PABS) and polyethylene glycol (PEG) were covalently attached to single-walled carbon nanotubes (SWNTs) to form water-soluble graft copolymers. Quantitative near-IR (NIR) spectroscopic studies of these SWNT graft copolymers indicate a water solubility of about 5 mg/mL, and atomic force microscopy studies show a fairly uniform length and diameter. On the basis of thermogravimetric analysis, the loading of SWNTs in the graft copolymers is estimated to be 30% for SWNT-PABS and 71%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
261
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(272 citation statements)
references
References 69 publications
(134 reference statements)
9
261
1
1
Order By: Relevance
“…The functionalized nanotubes tend to form a (meta)stable colloidal suspension, sterically stabilised by the osmotic pressure induced when functional groups from adjacent nanotubes move into the same region of space (section 2.3) [117] . Additionally, in some cases stabilization is achieved by electrostatic interactions between the functional groups [35] . Furthermore, the functional group-solvent interaction lowers the enthalpy of mixing and can increase the entropy of mixing (solvent configurational effects) resulting in a lower free energy of mixing.…”
Section: Functionalisationmentioning
confidence: 99%
See 1 more Smart Citation
“…The functionalized nanotubes tend to form a (meta)stable colloidal suspension, sterically stabilised by the osmotic pressure induced when functional groups from adjacent nanotubes move into the same region of space (section 2.3) [117] . Additionally, in some cases stabilization is achieved by electrostatic interactions between the functional groups [35] . Furthermore, the functional group-solvent interaction lowers the enthalpy of mixing and can increase the entropy of mixing (solvent configurational effects) resulting in a lower free energy of mixing.…”
Section: Functionalisationmentioning
confidence: 99%
“…Various methods to provide this repulsive potential have been explored. Nanotubes have been dispersed and stabilised with the aid of specific solvents [16][17][18][19][20][21][22][23][24] , acids [25,26] , macromolecules [27][28][29][30] and surfactants [31][32][33][34] as well as through covalent functionalisation strategies [35,36] . Such systems have been characterised by a range of techniques such as atomic force microscopy [37] , infra-red photoluminescence and absorbance spectroscopy [34] , viscometry [25] , small angle neutron scattering [32] to name but a few.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the results showed that 1.4 g of P7-SWCNT contains 1 g of SWCNT, which is equivalent to 2.62 g and 1.14 g of Pl-PEG 5000 and Pl-PEG 2000, respectively. 13 UV absorbance of the equivalent amounts of each compound in water was measured (UV-Vis spectrophotometer, CECIL CE 2021, 2000 series, Cambridge, UK) and showed equal values, indicating that the absorbance is due only to the SWCNT structure (and not to the functionalizing compounds). Various P7-SWCNT aqueous concentrations (over the range of 0.01-0.14 mg/mL) were then prepared for the construction of a standard calibration curve.…”
mentioning
confidence: 99%
“…After that, interest of biological applications such as nanobiodevices using hybrids of biomolecules and CNTs has been recognized. On the other hand, one of the recent progresses in nanocarbon technology is synthesis of variously functionalized SWNTs [4]. Some of the chemically modified SWNTs can be solved in water without attaching surfactants or biomolecules.…”
Section: Introductionmentioning
confidence: 99%